Low-power-consumption ultraviolet photodetector based on p-NiO/SiO2/n-ZnO - Jia, Menghan; Wang, Fang; Tang, Libin; Xiang, Jinzhong; Teng, Kar Seng; Lau, Shu Ping; Lü, Yanfei (Optics and laser technology, 2023)
•Ultraviolet photodetector based on thinfilm based p-NiO/SiO2/n-ZnO heterostructure is successfully fabricated for the first time.•A design of low-power-consumption photodetector is realized by using low-cost method.•Rectification ratio and rise time of the photodetector are 57 and 0.048 s, respectively.•Low dark current and good stability of the photodetector have been demonstrated. Ultraviolet (UV) photodetector has found extensive applications, ranging from optical communication to ozone sensing. Wide bandgap metal oxide heterostructures have gained significant interest in the development of UV photodetectors due to their excellent electronic and optical properties, as well as ease of fabrication. However, there are surface and interface issues at these heterostructures that have detrimental effects on device performance. In this work, UV photodetector consisting of p-NiO/SiO2/n-ZnO heterostructure was prepared by RF magnetron sputtering method. The device exhibited remarkable performances, such as having a rectification ratio of 57, responsivity (R) of 5.77 AW−1, external quantum efficiency (EQE) of 1.96 × 103% and rise time of 0.048 s at a low power consumption of −0.1 V under 365 nm UV irradiation. This work demonstrated a method for low-cost fabrication of photodetectors with rectification behavior and at low power consumption.